1999
DOI: 10.1016/s0022-5347(05)68065-2
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Ureteropyeloscopy for Lower Pole Caliceal Calculi

Abstract: Retrograde ureteropyeloscopy is a safe and effective surgical treatment for lower pole intrarenal calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(98 citation statements)
references
References 14 publications
9
83
1
5
Order By: Relevance
“…[10] In 1990s, successful results have been published for fURS in the treatment of urolithiasis from centers with high caseloads. Grasso and Ficazzola [11] reported a SFR of 94% and 95% for stones of ≤10 mm and 11-20 mm, respectively.…”
Section: Treatment Of Intrarenal Stones Less Than 2 CMmentioning
confidence: 98%
“…[10] In 1990s, successful results have been published for fURS in the treatment of urolithiasis from centers with high caseloads. Grasso and Ficazzola [11] reported a SFR of 94% and 95% for stones of ≤10 mm and 11-20 mm, respectively.…”
Section: Treatment Of Intrarenal Stones Less Than 2 CMmentioning
confidence: 98%
“…stone-free) on renal sonography with a minimum three-month follow-up. 17 Extreme anatomical variants, including a long infundibulum, acute infundibulopelvic angle, and a dilated collecting system, correlated with surgical failures. Of the 19 surgical failures eight were secondary to inability to access the lower pole and 11 were secondary to inability to render the patient stonefree.…”
Section: Discussionmentioning
confidence: 99%
“…[9] The spatial anatomy of the lower renal pole plays a significant role in the stone-free rate after both SWL and fURS treatments. [17,18] Grasso and Ficazzola [18] evaluated 90 stone burdens that were located in lower pole and treated with fURS and showed that success rates decrease significantly when the stone size exceeds 20 mm. Of the 19 failures, 8 were secondary to the inability to access the lower pole.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 19 failures, 8 were secondary to the inability to access the lower pole. [18] In another study, El-Nahas et al [19] compared fURS with SWL for the treatment of lower pole stones and showed that fURS had significantly higher success rates but no increase in the complication rates. In our study, the majority of the stones were located in the lower pole in both groups (52.5% vs. 49.5%).…”
Section: Discussionmentioning
confidence: 99%